A large-number and multilayer quantum walk using silicon nano-photonic chip - Wan, L. X. (2020)
We experimentally demonstrated 2D quantum walks in a Si3 N4 chip and study how different parameters affect light distribution. Such scalable quantum device will have a promising application in the field of quantum communication and simulation.